A pintura de Paul Cézanne como expressão de presença em Merleau-Ponty - Sousa, Tiago de Jesus (2018)
Paul Cézanne, one of the greatest modern painters, called by Pablo Picasso of The Great Master, is taken in this work as the fundamental reference of rupture with classic art, science and philosophy. It is intended here to describe how Maurice Merleau-Ponty sees in the work of the French painter a possibility of overcoming a positivist and idealistic philosophy that transforms everything into thought, without taking into account the primordial contact with the world. The idea that Cézanne's painting is taken as a possibility of expression of the gross or savage world is applied here in the sense that, by inhabiting this world and being part of it, the painter does not transform it into thought for painting, does not make a representation of the world on its canvas, but creates a world of its own, a result of the promiscuity between the seer and the visible, which makes possible through this creative act, the experience with Being as presence.